Mapping of Religious Moderation Literature in Higher Education: A Bibliometric Review - M. Nuzulul Ulum; Sunarto Sunarto; Baharudin Baharudin; Umi Hijriyah; Agus Susanti; Qonita Shabira (STAI Hubbulwathan Duri, 2025)
Religious moderation has become a critical focus in higher education, particularly in fostering social harmony and inclusive national identity. This study aims to analyze current trends in religious moderation research within the higher education sector and identify opportunities for future research development. A Systematic Literature Review (SLR) approach was utilized, guided by PRISMA protocols to ensure accuracy and relevance. A total of 160 publications were initially gathered from ERIC, Taylor Francis, and Mendeley databases indexed in Scopus. Based on defined inclusion criteria, 23 publications from 2019 to 2024 were selected for in-depth analysis. Bibliometric analysis was conducted using VOSviewer 1.6.20 software. Findings reveal fluctuating trends in religious moderation research, with a notable increase in publications during 2022, likely influenced by contemporary social issues and educational policies. Indonesia emerged as the leading contributor, followed by Jordan and Canada. Predominantly, qualitative and quantitative methodologies were employed. Thematically, research concentrated on radicalism, curriculum development, and religious tolerance. Density mapping further indicates a research gap in the exploration of nationalism within the context of religious moderation. The limited focus on nationalism suggests an opportunity for future research to bridge this gap and reinforce the role of religious moderation in cultivating inclusive national identity within higher education. This study underscores the need for continued and diversified research on religious moderation, emphasizing its potential to promote social cohesion and counter radical ideologies in academic environments.